Representations of Scenography in the Contemporary Theatrical Discourse in the “Imagine That " Play (Eurasian Journal of Humanities and Social Sciences, 2022)
There is no doubt that each of the arts has a material from which the aesthetic achievement is built, so the researcher found that theater art, especially the presentation, whose artistic achievement is based on the scenography discourse, so the researcher studied these representations in the scenography of theatrical discourse and divided them into four chapters, In the first chapter the research problem included in the following question: (What did the scenography shaped through its representations of the contemporary theatrical discourse “Imagine that”), so this is of cognitive importance as it provides an objective study for researchers in theatrical sciences at the level of directing design, as well as the goal of the research (getting to know the Scenography and its meaning in contemporary theatrical discourse ((imagine that)). And the first chapter ended with defining the terms. In the second chapter, the theoretical framework, as it included two sections. In the first topic, the researcher dealt with (the concept of scenography) from a general standpoint, and the second topic (the scenography of modern theater (pioneers - experiments)) and how these technical-physical representations were associated with theatrical art, and the chapter concluded with the most important indicators that resulted from the framework Theoretical, and then the third chapter, which included the procedures and consisted of the research community, the research sample and the research tool, the sample analysis, and finally the fourth chapter: it included the results, conclusions, recommendations and suggestions, and then the sources, references and summary in Arabic and English).